2020
DOI: 10.3390/genes11121428
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Heart Defects in Down Syndrome Is Associated with Single Nucleotide Polymorphisms in HAS 21 Interferon Receptor Cluster and VEGFA Genes

Abstract: Background: Congenital heart defects (CHDs) are present in about 40–60% of newborns with Down syndrome (DS). Patients with DS can also develop acquired cardiac disorders. Mouse models suggest that a critical 3.7 Mb region located on human chromosome 21 (HSA21) could explain the association with CHDs. This region includes a cluster of genes (IFNAR1, IFNAR2, IFNGR2, IL10RB) encoding for interferon receptors (IFN-Rs). Other genes located on different chromosomes, such as the vascular endothelial growth factor A (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Sample size was determined a priori based on effect sizes of previous studies (e.g., human studies) or by post hoc analyses to ensure >80% power was achieved to reduce type II error (e.g., (HSA21) that may contribute to risk of congenital heart defects (CHDs) in humans with trisomy 21 (T21, yellow), genes with functional evidence whose triplication is necessary or sufficient to 5 increase incidence of CHDs in mouse models of Down syndrome (DS, blue), and genes with supporting evidence in both humans and mouse models of DS (green). Relative cytogenetic locations and number of protein-coding genes (bold) are indicated along ideogram of the q arm for HSA21 colored according to Giemsa banding (3,16,23,24,(56)(57)(58).…”
Section: Statistical Analysis and Results Visualizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample size was determined a priori based on effect sizes of previous studies (e.g., human studies) or by post hoc analyses to ensure >80% power was achieved to reduce type II error (e.g., (HSA21) that may contribute to risk of congenital heart defects (CHDs) in humans with trisomy 21 (T21, yellow), genes with functional evidence whose triplication is necessary or sufficient to 5 increase incidence of CHDs in mouse models of Down syndrome (DS, blue), and genes with supporting evidence in both humans and mouse models of DS (green). Relative cytogenetic locations and number of protein-coding genes (bold) are indicated along ideogram of the q arm for HSA21 colored according to Giemsa banding (3,16,23,24,(56)(57)(58).…”
Section: Statistical Analysis and Results Visualizationmentioning
confidence: 99%
“…S7 ) ( 3, 16, 23, 24, 56, 57 ). Notably, single nucleotide polymorphisms in IFNGR2 and IL10RB have been associated with risk of CHD in DS ( 58 ). Nevertheless, our results are the first demonstration that normalization of Ifnr copy number is sufficient to rescue this phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…DNA were extracted using a salting-out protocol and DNA quality was verified by 260/280 nm absorbance ratio and gel electrophoresis as previously reported [ 49 ]. SNP typing was performed using an on-demand assay developed by KBioscience Ltd. (Middlesex, UK) and based on homogeneous FRET (Fluorescence Resonance Energy Transfer) analysis on the products of a specific allele PCR (Kaspar) [ 50 , 51 ]. SNPs are listed in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Finally, as has been proposed, mutations and polymorphisms may contribute to the heterogeneity of DS phenotypes, such as the ones observed in the context of CHD. Balistreri et al studied the relationship between SNPs in four interferon receptors ( IFNAR1 , IFNAR2 , IFNGR2 , IL10RB ) and the VEGFA genes, and CHD in subjects with DS ( Balistreri et al, 2020 ). The interferon receptor genes belong to a cluster located in a 3.7 Mb critical genomic region associated with DS heart defects in the Ts1Cje DS mouse model ( Liu et al, 2014 ).…”
Section: Genetics Of Heart Disease In Dsmentioning
confidence: 99%
“…Although VEGFA is located in another chromosome, its overexpression in mice embryos triggers severe heart development abnormalities ( Miquerol et al, 2000 ). In this regard, Balisteri et al , found that IFNAR2 and IL10RB SNP were related with heart disorders in subjects with DS, whereas VEGF SNP were less prevalent in subjects with CHD ( Balistreri et al, 2020 ). Similarly, Joziasse et al , identified a SNP in the ALK2 receptor , a member of the TGF-β superfamily, in a patient with DS and CHD, resulting in an H286D substitution.…”
Section: Genetics Of Heart Disease In Dsmentioning
confidence: 99%